2020
DOI: 10.3389/fvets.2020.552251
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Atopic Dermatitis and Diet on the Skin Transcriptome in Staffordshire Bull Terriers

Abstract: Canine atopic dermatitis (CAD) has a hereditary basis that is modified by interactions with the environment, including diet. Differentially expressed genes in non-lesional skin, determined by RNA sequencing before and after a dietary intervention, were compared between dogs with naturally occurring CAD (n = 4) and healthy dogs (n = 4). The dogs were fed either a common commercial heat-processed high carbohydrate food (kibble diet) (n = 4), or a non-processed high fat food (raw meat-based diet) (n = 4). At the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 109 publications
0
8
0
Order By: Relevance
“…Notably, the transcriptional regulation of many of these markers was modulated by nutraceutical exposure [ 29 ] because it involves binding of toll-like receptors and downregulation of the predominately Th2-mediated allergic response [ 30 ]. It is now accepted that the regular utilization of food supplements (polyphenols, essential fatty acids, vitamins or probiotics) has beneficial effects on animals [ 31 ]. Epidemiological data regarding the development of cAD and the analysis of the impact on patients’ lives today justify the need to identify new and sustainable therapeutic strategies aimed at counteracting both the development and complications of atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the transcriptional regulation of many of these markers was modulated by nutraceutical exposure [ 29 ] because it involves binding of toll-like receptors and downregulation of the predominately Th2-mediated allergic response [ 30 ]. It is now accepted that the regular utilization of food supplements (polyphenols, essential fatty acids, vitamins or probiotics) has beneficial effects on animals [ 31 ]. Epidemiological data regarding the development of cAD and the analysis of the impact on patients’ lives today justify the need to identify new and sustainable therapeutic strategies aimed at counteracting both the development and complications of atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Of relevance, the transcriptional regulation of many of these markers was modulated by the nutraceutical exposure. It is well-established that the regular use of dietary supplements, such as essential fatty acids (EFAs), polyphenols, probiotics, or vitamins, has benefits for atopic animals (28)(29)(30)(31)(32). Their mechanisms of action in canine AD are not completely elucidated but may involve binding of toll-like receptors and downregulation of the predominately Th2mediated allergic response (3,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely assumed that early life dietary exposures might be a major contributor to the development of AD in dogs later in life 11 . Furthermore, it has been reported that gene expression may constantly be epigenetically regulated by the early diet, 19‐21 via promoting gut microbiota diversity 22 . Recent studies have demonstrated that the composition of the gut environment, including both its diversity in microbes and chemical compounds, differs between healthy and AD patients 23‐25 …”
Section: Discussionmentioning
confidence: 99%